2003
DOI: 10.1080/10288457.2003.10740546
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Science—Do teachers have the understandings they are expected to teach?

Abstract: South Africa is introducing Outcomes Based Education as an approach to teach the new Curriculum 2005 (C2005). The new curriculum contains exciting new aspects for the Natural Sciences. For example, in addition to learning traditional science subject matter, children are expected to develop also an understanding of the 'changing and contested nature of knowledge in the natural sciences', i.e. of the 'Nature of Science' (NOS). Since curriculum reform depends crucially on the teachers, it is important to find out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…This is in spite of the fact that many of the school teachers in South Africa, as some of the studies clearly show (e.g. Dekkers & Mnisi, 2003), are not equipped with the requisite content and pedagogical knowledge to explicitly teach about the NOS. Our assertion is that, there appears to be an uncritical and sheepish legitimisation of the superiority of so-called explicit approaches.…”
Section: The International Nos and Iks Programmes And Research In Soumentioning
confidence: 67%
See 2 more Smart Citations
“…This is in spite of the fact that many of the school teachers in South Africa, as some of the studies clearly show (e.g. Dekkers & Mnisi, 2003), are not equipped with the requisite content and pedagogical knowledge to explicitly teach about the NOS. Our assertion is that, there appears to be an uncritical and sheepish legitimisation of the superiority of so-called explicit approaches.…”
Section: The International Nos and Iks Programmes And Research In Soumentioning
confidence: 67%
“…All the reviewed empirical studies (Dekkers & Mnisi, 2003;Linneman et al, 2003;Dekkers, 2006;Ogunniyi, 2004Ogunniyi, , 2006Webb et al, 2005;Ramsuran, 2005) done on the NOS and IKS; have used, largely qualitative methodological approaches. This is not a surprising observation.…”
Section: Methodological Underpinningsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a South African study by Dekkers and Mnisi (2003) in the Limpopo Province, which investigated teachers' understanding of the nature of science that is an integral component of multidimensional scientific literacy, found that the majority of teachers surveyed through a questionnaire had an inadequate understanding of the nature of science. In fact many of these teachers who were interviewed expressed common myths on the nature of science identified by McComas (1998).…”
Section: The Concept Of Scientific Literacy and Its Implications For mentioning
confidence: 98%
“…Postmodernists delineate science as one of the ways of knowing, which is influenced by the social and cultural values of the society, and emphasize the multiple methods used by scientists. In a nutshell, the unsettled academic discussions about science indicate that there is no single NOS to be endorsed by all scholars [1,17]. Some even go to say that there simply is no such thing as NOS [19].…”
Section: Introductionmentioning
confidence: 99%